E-learning from the perspective of right to education - Cakmak, Esra; Yilmaz, Seher Merve (ELSEVIER SCIENCE BV, 2014)
The object of this study is to examine whether Computer Education and Instructional Technologies (CEIT) students' views differentiate according to the mode of course delivery: face-to-face or e-learning. As a sample, four CEIT students getting courses with e-learning and seven CEIT students getting courses with face-to-face mode are chosen. As a data collection tool interview questions are prepared by researchers. Data is analyzed in two dimensions: students' views about the process and result of e-learning and face-to-face learning from the perspective of right to education. When students' views are analyzed, it is understood that e-learning mode has more disadvantages than advantages for both groups because of the lack of substructure. (C) 2013 The Authors. Published by Elsevier Ltd.
Keywords: E-learning; face-to-face learning; right to education; Computer Education and Instructional Technologies (CEIT); Education & Educational Research